2014
DOI: 10.1523/jneurosci.0723-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Repetitive Transcranial Magnetic Stimulation Improves Abnormal Visual Cortical Circuit Topography and Upregulates BDNF in Mice

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is increasingly used as a treatment for neurological and psychiatric disorders.Although the induced field is focused on a target region during rTMS, adjacent areas also receive stimulation at a lower intensity and the contribution of this perifocal stimulation to network-wide effects is poorly defined. Here, we examined low-intensity rTMS (LI-rTMS)-induced changes on a model neural network using the visual systems of normal (C57Bl/6J wild-type, n ϭ 22) and ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
143
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(167 citation statements)
references
References 99 publications
15
143
6
Order By: Relevance
“…Based on previous in vivo parameters (Rodger et al, 2012; Makowiecki et al, 2014), we aimed to obtain a maximal magnetic field strength of 10 mT at the target tissue, with a rise-time of less than 100 μs and pulse length of 300 μs (Grehl et al, 2015). Because pulse shape alters the efficiency of neuromodulation (Goetz et al, 2016), we used a symmetric trapezoidal pulse with the same rate of current rise-and fall, in keeping with LFMS in humans (Rohan et al, 2014).…”
Section: Methods and Results: Stimulation Device Design Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous in vivo parameters (Rodger et al, 2012; Makowiecki et al, 2014), we aimed to obtain a maximal magnetic field strength of 10 mT at the target tissue, with a rise-time of less than 100 μs and pulse length of 300 μs (Grehl et al, 2015). Because pulse shape alters the efficiency of neuromodulation (Goetz et al, 2016), we used a symmetric trapezoidal pulse with the same rate of current rise-and fall, in keeping with LFMS in humans (Rohan et al, 2014).…”
Section: Methods and Results: Stimulation Device Design Constructionmentioning
confidence: 99%
“…Newer low- or pulsed-field magnetic stimulation (LFMS, PMF) delivers diffuse low-intensity stimuli (μT-mT range, E ≤ 1 V/m) that are also biologically effective: modifying cortical function (Capone et al, 2009; Robertson et al, 2010), brain oscillations (Cook et al, 2004; Modolo et al, 2013) and metabolism (Volkow et al, 2010), as well as neurological dysfunction (Martiny et al, 2010; Rohan et al, 2014). We have combined these two approaches creating a small rodent coil to deliver focal low-intensity magnetic stimulation (LI-rTMS), and found that 2 weeks of LI-rTMS can reorganize neural circuits (Rodger et al, 2012; Makowiecki et al, 2014). However, although LFMS now forms an additional tool for NIBS therapies (Shafi et al, 2014), the mechanisms underlying the effects of low intensity magnetic stimulation remain ill-defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies all report significant MEP suppression at the upper end of the IO curve (150 -170% RMT) following low frequency rTMS (1 Hz) (Gangitano et al 2002;Hortobagyi et al 2009;Muellbacher et al 2000). Pharmacological studies show that both cTBS and 1 Hz rTMS induce NMDA receptor-dependant LTD-like plasticity (Chen et al 1997;Huang et al 2007), albeit via the modulation of different cortical circuits; studies recording descending volleys from the epidural space show that cTBS primarily suppresses the I1 wave (Di Lazzaro et al 2005), while 1 Hz rTMS primarily suppresses late I waves (Hill et al 1996;Makowiecki et al 2014). The current results suggest that the upper end of the MEP IO curve is optimal for probing cTBS-induced LTD-like plasticity.…”
Section: Discussionmentioning
confidence: 98%
“…It is less likely that action potentials will be induced at this field strength but low-intensity magnetic stimulation has been shown to affect neuronal morphology, development and survival, probably due to release of calcium ions from intracellular stores (Rodger et al . 2012; Makowiecki et al . 2014; Grehl et al .…”
Section: Discussionmentioning
confidence: 99%